A new scoliid wasp in the Early Cretaceous Crato Formation in Brazil (Hymenoptera: Scoliidae) - Nel, André; Escuillie, François; Garrouste, Romain (Zootaxa, 2013)
The new genus and species of scoliid wasp Araripescolia magnifica Nel, Escuillie & Garrouste, gen. et sp. nov. is described from the Early Cretaceous Crato formation in Brazil. It seems to be more closely related to the modern Campsomerinae than to the other Cretaceous Scoliidae: Archaeoscoliinae and Proscoliinae.